Young male and female coping style in negative life events - Komalavani, Subramaniam (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The main purpose of the study is to explore on the types of negative life events and the various coping styles used among young adults at Kota Samarahan. Besides that, aspect of differences among gender in dealing with a particular negative life event is also taken into consideration in this study. The research was qualitative study and semi-structured interview questions were used. The number of informants involved in this study were ten, 5 male and 5 female respectively. All respondents were interviewed based on the research questions formed earlier of this study. The age of respondents basically revolves around 21-25 as only young adults were selectively chosen. The data collected from the interview was analysed based on the thematic analysis. Analysis shows that females were prone towards friendship problems and they tended to deal it using emotional-focussed coping such as crying, whereas male were reported to experience cases much related to relationship problems and tended to cope with action based coping style like confronting and play games. The findings from this research would be useful for future research to further enhance the study on impact of negative life events in much varied demographic profile and larger sample size.